Pelatihan Penggunaan Web Server Pada SOS Children’s Villages Medan - Agustin, Fhery; M. Fahriansyah B. (Publikasi Pengabdian Masyarakat, 2022)
The use of a Web Server is a must in testing web-based applications that have been made by programmers. This test aims to see if the application made can run perfectly. The role of the web server is to simulate the actual conditions when a web-based application runs on a browser properly using the internet network. So that the application testing will really be like in online conditions even though it is tested using a stand alone computer. Likewise, the testing of the database used is also network-based which must be able to run perfectly on the browser and can be accessed via the network. There are several web server applications that have been tested and can run well, which will be introduced in this training are Appserv and the database is based on phpmyadmin.